Competing on Analytics : The New Science of Winning - Davenport, Thomas H. 1954- and Harris, Jeanne G. (Boston Harvard Business School Press, 2007)
"In Competing on Analytics: The New Science of Winning, Thomas H. Davenport and Jeanne G. Harris argue that the frontier for using data has shifted dramatically. Leading companies are doing more than just collecting and storing information in large quantities. They're now building their competitive strategies around data-driven insights that are, in turn, generating impressive business results. Their secret weapon? Analytics: sophisticated quantitative and statistical analysis and predictive modeling supported by data-savvy senior leaders and powerful information technology."--Jacket.
Include Notes and Index
Keywords: Business intelligence -- Business mathematics